TANAMI: Tracking Active Galactic Nuclei with Austral Milliarcsecond Interferometry - II. Additional Sources - Muller, C; Kadler, M; Ojha, R; Schulz, R; Trustedt, J; Edwards, PG; Ros, E; Carpenter, B; Angioni, R; Blanchard, J; Bock, M; Burd, PR; et al. (EDP Sciences, 2017)
Context. TANAMI is a multiwavelength program monitoring active galactic nuclei (AGN) south of −30◦ declination including highresolution Very Long Baseline Interferometry (VLBI) imaging, radio, optical/UV, X-ray and γ-ray studies. We have previously published first-epoch 8.4 GHz VLBI images of the parsec-scale structure of the initial sample. In this paper, we present images of 39 additional sources. The full sample comprises most of the radio- and γ-ray brightest AGN in the southern quarter of the sky, overlapping with the region from which high-energy (> 100 TeV) neutrino events have been found. Aims. We characterize the parsec-scale radio properties of the jets and compare with the quasi-simultaneous Fermi/LAT γ-ray data. Furthermore, we study the jet properties of sources which are in positional coincidence with high-energy neutrino events as compared to the full sample. We test the positional agreement of high-energy neutrino events with various AGN samples. Methods. TANAMI VLBI observations at 8.4 GHz are made with Southern-Hemisphere radio telescopes located in Australia, Antarctica, Chile, New Zealand, and South Africa. Results. Our observations yield the first images of many jets below −30◦ declination at milliarcsecond resolution. We find that γ-ray loud TANAMI sources tend to be more compact on parsec-scales and have higher core brightness temperatures than γ-ray faint jets, indicating higher Doppler factors. No significant structural difference is found between sources in positional coincidence with high-energy neutrino events and other TANAMI jets. The 22 γ-ray brightest AGN in the TANAMI sky show only a weak positional agreement with high-energy neutrinos demonstrating that the > 100 TeV IceCube signal is not simply dominated by a small number of the γ-ray brightest blazars. Instead, a larger number of sources have to contribute to the signal with each individual source having only a small Poisson probability for producing an event in multi-year integrations of current neutrino detectors.
Keywords: galaxies: active -– galaxies: jets -– galaxies: nuclei -– radio continuum: galaxies – techniques: high angular resolution